Immunomodulation in Plasmodium falciparum malaria: experiments in nature and their conflicting implications for potential therapeutic agents. Issue 11 (November 2012) - Frosch, Anne EP; John, Chandy C
Effective Plasmodium falciparum immunity requires a precisely timed and balanced response of inflammatory and anti-inflammatory immune regulators. These responses begin with innate immune effectors and are modulated over the course of an infection and between episodes to limit inflammation. To date, there are no effective immunomodulatory therapies for severe malaria. Some of the most potent immunomodulators are naturally occurring infections, including helminthic and chronic viral infections. This review examines malaria coinfection with these organisms, and their impact on malaria morbidity and immune responses. Overall, there is compelling evidence to suggest that chronic coinfections can modulate deleterious malaria-specific immune responses, suggesting that therapeutic agents may be effective if utilized early in infection. Examination of the mechanisms of these effects may serve as a platform to identify more targeted and effective malaria immunomodulatory therapeutics.